Cool cat bringing 1940s and 1950s flair to your wardrobe - Luster, Lori (North Mankato, Minnesota Capstone Press, 2014)
"Describes the fashion trends of the 1940s and 1950s, including step-by-step instructions on how to get the looks today"--
A gift from book Africa
Arts
1 2 13 15
Keywords: Dress accessories -- Juvenile literature; Fashion -- History -- 20th century -- Juvenile literature